HOLDING GAINS ON FIXED ASSETS - A DEMURRER. - Zeff, Stephen A.; Maxwell, W. David (The Accounting Review, 1965)
Accountant and economist are a sensible combination on matters of income determination, as Professors Robert L. Dickens and John O. Blackburn demonstrated, that their several-pronged analysis demolishes the case for replacement cost as an ingredient in accounting net income is, however, deserving of a demurrer. This present article is a criticism of their criticism, the purpose being to return the argument to what the economists regard as its proper grounds. The criticisms embrace three areas, methodology, economic theory, and accounting theory. The methodological criticisms are, of course, general and independent of the subject matter treated. The criticisms on economic theory refer primarily to economic concepts which underlie many of the questions discussed by Dickens and Blackburn and are, of course, specific to economic theory and its applications. The criticisms on accounting theory are principally concerned with the charges, both express and implied, by Dickens and Blackburn that the use of replacement cost is incompatible with the informational needs of stockholders, and significantly less conventional than the use of conventional accounting, thus being an invitation to easy manipulation of accounting data by managers.